Bone metabolism assessment in children with chronic arthritides - M M Kostik; L M Vorontsov; V I Larionova (Научно-практическая ревматология, 2007)
Bone mineral density (BMD), bone biochemical markers, influence of inflammation and glucocorticoid administration on bone metabolism in 70 children with chronic arthritis were studied. Osteopenia was detected by dual energetic X-ray absorptiometry L1-L4 in 18,7% children. Disease duration enhanced osteopenia frequency. Low BMD was associated with low levels of total calcium and osteocalcine. We revealed that BMD parameters positively correlated with anthropometry and negatively correlated with total alkaline phosphatase activity and osteocalcine and p — CrossLaps levels. As inflammatory activity, as glucocorticoids decreased BMD parameters and bone biochemical markers levels. The most negative changes were been revealed in children with systemic variant of arthritis and little changes in children with monooligoarthicular variant of arthritis. Conclusion. BMD, levels of bone biochemical markers, osteopenia risk realization depend on arthritis duration, inflammatory activity, disease degree, number of joints, involved in arthritis and therapy.